Galectin-3 and prohibitin 1 are autoantigens in IgG4-related cholangitis without clear-cut protective effects against toxic bile acids - Kersten, Remco; Trampert, David C.; Hubers, Lowiek M.; Tolenaars, Dagmar; Vos, Harmjan R.; van de Graaf, Stan F. J.; Beuers, Ulrich (Frontiers in Immunology, 2024)
Background and aims IgG4-related cholangitis (IRC) is the hepatobiliary manifestation of IgG4-related disease, a systemic B cell-driven fibro-inflammatory disorder. Four autoantigens have recently been described in IgG4-RD: annexin A11, galectin-3, laminin 511-E8, and prohibitin 1. We have previously reported a protective role of annexin A11 and laminin 511-E8 in human cholangiocytes against toxic bile acids. Here, we explored the potentially protective role of the carbohydrate-binding lectin galectin-3 and the scaffold proteins prohibitins 1 and 2. Methods Anti-galectin-3, anti-prohibitin 1 and 2 autoantibody positivity in IRC and healthy and disease (primary sclerosing cholangitis (PSC)) control sera was assessed by ELISA/liquid chromatography–tandem mass spectrometry (LC-MS/MS). Human H69 cholangiocytes were subjected to short hairpin RNA (shRNA) knockdown targeting galectin-3 (LGALS3), prohibitin 1 (PHB1), and prohibitin 2 (PHB2). H69 cholangiocytes were also exposed to recombinant galectin-3, the inhibitor GB1107, recombinant prohibitin 1, and the pan-prohibitin inhibitor rocaglamide. Protection against bile acid toxicity was assessed by intracellular pH (pHi) measurements using BCECF-AM, 22,23-3H-glycochenodeoxycholic acid (3H-GCDC) influx, and GCDC-induced apoptosis using Caspase-3/7 assays. Results Anti-galectin-3 autoantibodies were detected in 13.5% of individuals with IRC but not in PSC. Knockdown of LGALS3 and galectin-3 inhibition with GB1107 did not affect pHi, whereas recombinant galectin-3 incubation lowered pHi. LGALS3 knockdown increased GCDC-influx but not GCDC-induced apoptosis. GB1107 reduced GCDC-influx and GCDC-induced apoptosis. Recombinant galectin-3 tended to decrease GCDC-influx and GCDC-induced apoptosis. Anti-prohibitin 1 autoantibodies were detected in 61.5% and 35.7% of individuals with IRC and PSC, respectively. Knockdown of PHB1, combined PHB1/2 KD, treatment with rocaglamide, and recombinant prohibitin 1 all lowered pHi. Knockdown of PHB1, PHB2, or combined PHB1/2 did not alter GCDC-influx, yet knockdown of PHB1 increased GCDC-induced apoptosis. Conversely, rocaglamide reduced GCDC-influx but did not attenuate GCDC-induced apoptosis. Recombinant prohibitin 1 did not affect GCDC-influx or GCDC-induced apoptosis. Finally, anti-galectin-3 and anti-prohibitin 1 autoantibody pretreatment did not lead to increased GCDC-influx. Conclusions A subset of individuals with IRC have autoantibodies against galectin-3 and prohibitin 1. Gene-specific knockdown, pharmacological inhibition, and recombinant protein substitution did not clearly disclose a protective role of these autoantigens in human cholangiocytes against toxic bile acids. The involvement of these autoantibodies in processes surpassing epithelial secretion remains to be elucidated.